Terahertz sensing with optimized Q/V eff metasurface cavities - Gupta, Manoj (2021)
Confinement of electromagnetic radiation in a subwavelength cavity is an important platform for strong light–matter interaction as it enables efficient design of photonic switches, modulators, and ultrasensitive sensors. Metallic metasurfaces consist of an array of planar cavities that allow easy access to confined electromagnetic modes on the surface. However, the radiative and nonradiative losses limit the quality factor (Q) of the resonantly confined mode. Therefore, metasurface designs with effectively low mode volume (Veff) cavities become extremely important for enhancing the photonic density of states. Here, a symmetric Lorentzian resonant metasurface with lower Veff is demonstrated as compared to asymmetric Fano resonators. Lower mode volume and optimized Q/Veff metasurfaces reveal enhanced sensitivity for ultrathin analyte overlayers deposited on metasurfaces signaling enhanced light–matter interaction. Such metasurfaces with tightly confined electromagnetic modes could find wide range of applications in the development of terahertz metadevices including ultrasensitive sensors, bandpass filters, and energy-efficient modulators.